Analisis Kesejahteraan Petani Tembakau Dampak Politik Kebijakan Pemerintah di Masa Pandemi - Fachmi Ibrahim; Rasmira; Khori Suci Maifianti (BULLET : Jurnal Multidisiplin Ilmu, 2022)
During the Covid-19 pandemic various problems faced by farmers such as price stability, distribution, and uncertainty of purchasing agricultural products. Therefore, it is required the government make policies that support farmers. Agriculture is one of the sectors that continue to exist during the Covid-19 pandemic, proven in the second quarter of 2020 to contribute 15.46% to the total gross domestic product (GDP) and play an important role in the Indonesian economy. The first policy issued by the government in the form of social and physical distancing make the movement of people limited. The dynamics of the development of Covid-19 are unstoppable so that the government issued a Large-Scale Social Restriction Policy (PSBB) that further lowers the wheels of the Indonesian economy. Whatever policy is issued have an impact on agricultural products to disrupt the welfare of farmers. The aim of the study is to analyze the well-being of tobacco farmers related to government policies during the Covid-19 pandemic with a case study approach and qualitative methods of phenomenology. The results showed there were various impacts due to the Covid-19 pandemic, but government policies related to agriculture during the Covid-19 pandemic have not sided with tobacco farmers, therefore, policies are needed that are not only top-down but based on the analysis of the situation and needs of the community.